Apolipoprotein (a) phenotypes and lipoprotein (a) concentrations in patients with type III hyperlipoproteinaemia - Feussner, Giso; Feussner, Vera; Ziegler, Reinhard (Journal of internal medicine, 1994)
Abstract. Objectives. The familial lipoprotein disorder type III hyperlipoproteinaemia (HLP) carries a marked increase in the risk of accelerated and premature atherosclerosis, but there is considerable variation amongst affected individuals in their susceptibility to cardiovascular disease (CVD). Therefore, it was the aim of our study to investigate the possible influence of lipoprotein (a) [Lp(a)] in the pathogenesis of type III HLP. Design. Apolipoprotein (a) [apo(a)] phenotypes and Lp(a) concentrations were determined in patients with the disease and in an appropriate control group. Setting. University out-patient lipid disorder clinic. Subjects. Seventy-six apoE-2 homozygous patients with type III HLP and 76 normolipidaemic and healthy age- and sex-matched controls. Main outcome measures. The frequencies of different apo(a) phenotypes and their correlations with Lp(a) serum concentrations were determined in patients and controls. Results. Lp(a) concentrations were not significantly different in type III HLP patients (14.1±19.1 mg dl-1) as compared with the controls (13.3±16.2 mg dl-1; P = 0.549, NS). In addition, there was no significant difference in apo(a) phenotype frequencies amongst both groups (0.2 > P > 0.1). Conclusions. We conclude that the apo(a) polymorphism does not participate (to a significant extent) in the phenotypical expression of type III HLP.